'A taste of this lively language': attitudes towards languages other than English in lonely planet phrasebooks. Issue 3 (3rd July 2017) - Hallett, Richard W.
ABSTRACT: This paper addresses language attitudes towards non-English, mostly non-Western, languages in the phrasebooks published by Lonely Planet for English-speaking travellers to multilingual regions of the Global South. Specifically, this paper examines attitudes towards the languages exemplified in Lonely Planet's second edition of Africa: Phrasebook and Dictionary (2013 ), second edition of India: Phrasebook and Dictionary (2014 ), fourth edition of Pidgin: Phrasebook (2015 ), third edition of Hill Tribes (2008), second edition of South Pacific Phrasebook (2008), and third edition of Southeast Asia: Phrasebook and Dictionary (2013 ). In so doing, this research argues that the phrasebooks describe these languages and their speakers as exotic, monolithic, simplistic, and deterministic; and construct the traveller's efforts to use these languages as acts of benevolence.